Desenvolvimento e a regulação do mercado livre de energia no Brasil - Silva, Vinícius Radetzke da (2017)
The development of the Free Energy Market in Brazil gained considerable importance due to a series of recent transformations in Brazilian politics. For a long time, investments were not made in this sector, causing a delay in the energy matrix of Brazil. As a result, the government sought an alternative to change the sector’s deficit, attract new investors and promote capitalist price competition. The regulation provided by law aimed at framing Brazil in the policy of the free market of energy, giving the freedom of companies to fit in requirements that allow to consume electricity of other generating companies, either by means of celebration of exclusive contracts, called captives, or by buying at auctions of competition managed by legislators of the sector and also by the leftover market energy, called the free market spot. In this way, this study aimed to present the development of the Brazilian Free Energy Market and to make a comparison between the forecast of the average prices of the settlement of energy differences (PLD) and the values sold in the second half of 2015. For this purpose, From May of 2003 to June of 2015. The study was developed through bibliographical research, of the exploratory and quantitative type. The data were obtained with the aid of information from the Electric Energy Trading Chamber through a time series of the PLD in the free market of electric energy. For the prediction, the multiplicative Holt Winters method was the best fit, among the models studied, to the PLD values, and can be used as a basic reference for consumers and/or power generators related to production scheduling, representing the Reducing costs and providing increased competitiveness for products and services that are produced per hour.